2021
DOI: 10.18844/cjes.v16i4.6028
|View full text |Cite
|
Sign up to set email alerts
|

Technological pedagogical content knowledge as a predictor of physical education and sports teachers' evaluations of distance education

Abstract: The aim of this study is to reveal whether physical education and sports teachers' technological pedagogical knowledge levels and some variables are significant predictors of distance education evaluation levels. The correlational design, in which the direction and strength of the relationship between more than one variable were investigated, was used in the study. The research group consists of 213 physical education and sports teachers. The data of the research were collected with the Technologic Pedagogical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
5
0
3
Order By: Relevance
“…Meanwhile, the e-sports business will focus its future research on e-sports game standards, 5G e-sports mode, professionalized e-sports sports, and e-sports education and culture. One of the objectives is to determine if technical, pedagogical knowledge levels and other variables are excellent predictors of how well distance education students will do in school [ 10 ]. The authors of [ 11 ] suggested a model-based approach to physical education, which incorporated a variety of diverse models for the first time.…”
Section: Related Workmentioning
confidence: 99%
“…Meanwhile, the e-sports business will focus its future research on e-sports game standards, 5G e-sports mode, professionalized e-sports sports, and e-sports education and culture. One of the objectives is to determine if technical, pedagogical knowledge levels and other variables are excellent predictors of how well distance education students will do in school [ 10 ]. The authors of [ 11 ] suggested a model-based approach to physical education, which incorporated a variety of diverse models for the first time.…”
Section: Related Workmentioning
confidence: 99%
“…Educational programs have also entered into new searches in this process. During distance education period, technological pedagogical knowledge degrees of teachers have developed (Akkaya, 2021). Teachers prepared course materials for an effective implementation of remote learning when school closure measures were taken.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the e-sports business will focus its future research on e-sports game standards, 5G e-sports mode, professionalized e-sports sports, and e-sports education and culture. One of the objectives is to determine if technical, pedagogical knowledge levels and other variables are excellent predictors of how well distance education students will do in school [10]. e authors of [11] suggested a model-based approach to physical education, which incorporated a variety of diverse models for the first time.…”
Section: Related Workmentioning
confidence: 99%